Epidemiology of esophageal atresia. Issue 4 (16th May 2013) - Sfeir, R.; Michaud, L.; Salleron, J.; Gottrand, F.
Summary Esophageal atresia (EA) is a rare congenital malformation consisting of a lack of continuity between the upper and lower esophageal pouches, frequently associated with tracheoesophageal fistula. The prevalence of such rare abnormalities is established by global birth surveillance programs over the world. EUROCAT is a European program covering 1.7 million births since its creation. The prevalence of EA in Europe seems stable over decades. The National Birth Defects Prevention Network in the USA also shows a stable prevalence with a wide range between states or regions. In France, with the implementation of the national rare diseases plan, a reference center for congenital abnormalities of the esophagus was created in 2006 and a national registry for EA began patient inclusion in 2008. This has resulted in the establishment of the national live birth prevalence for EA, prenatal diagnosis rates, and clinical characteristics of EA patients, early survival, and early morbidity. Prevalence rates seem stable all over the world since many decades. Continuous surveillance of congenital abnormalities and specific registries are useful for epidemiologic data but also for public health authorities for helping families of rare diseases patients.